Some Solutions for Coping and Raising Awareness about Mental Health when Accessing Information about the Covid-19 Pandemic on Facebook - Nguyen, Tan Khang; Thu Mai Ly, Dang; Nguyen , Hoang Anh Thu (Fakultas Ekonomi dan Ilmu Sosial Program Studi Ilmu Komunikasi Universitas AMIKOM Yogyakarta, 2024)
The study was conducted to explore the general mental health status of students when accessing information about the COVID-19 pandemic on the Facebook social media platform. The main methods used in the research were surveys through questionnaires and document analysis. The quantitative results highlight the mental health issues of students, thereby proposing groups of solutions to help students cope and raise awareness to protect mental health not only during social distancing periods due to the COVID-19 pandemic but also to equip them with knowledge for self-protection in the future.